2001
DOI: 10.1007/s003810000438
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic third ventriculostomy in dysmorphic brains

Abstract: Neuroendoscopic third ventriculostomy (NTV) has superseded shunting as the treatment of choice in non-communicating hydrocephalus. Intracranial developmental anomalies have been considered to be relative contraindications for this procedure. We present one patient with a Dandy-Walker malformation and another with septo-optic dysplasia who presented with hydrocephalus. An NTV was performed successfully in both patients using a flexible neuroendoscope and utilising transendoscopic Doppler ultrasound to ensure a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…Dysmorphic brains already present prior to ventriculostomy were not found to be a predictor for poor outcome in our series compared to other studies [3,19]. Size of the third ventricular floor and ventricle ratio was also not found to be a predictor of outcome as suggested by various studies [4,7,13,18]. Size or presence of lumbar meningomyelocele defects was also not a predictor for bad outcome as published recently [14,19].…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Dysmorphic brains already present prior to ventriculostomy were not found to be a predictor for poor outcome in our series compared to other studies [3,19]. Size of the third ventricular floor and ventricle ratio was also not found to be a predictor of outcome as suggested by various studies [4,7,13,18]. Size or presence of lumbar meningomyelocele defects was also not a predictor for bad outcome as published recently [14,19].…”
Section: Discussioncontrasting
confidence: 40%
“…Preoperative meningitis and/or ventricular haemorraghe was found to be an important predictor. Numerous studies [1,5,[15][16][17][18]20] support this. Overall, our findings differ from one paper [20] which dealt with normal pressure hydrocephalus and other publications on abnormal anatomy and third ventricular floor width [3,4].…”
Section: Discussionmentioning
confidence: 53%
“…46 One patient suffered haemorrhage after third ventriculostomy and thalamic/pineal tumour biopsy; subsequent imaging revealed a thoracolumbar spinal subdural haematoma as well. 39 Tumour recurrence in the ventriculoscope tract after biopsy and ventriculostomy has been reported, and should be considered when planning postbiopsy radiation. 88 Bradycardia during fenestration and during reversal of neuromuscular blockade occurs with greater frequency during third ventriculostomy compared with other neuroendoscopic procedures.…”
Section: Complicationsmentioning
confidence: 98%
“…38 Dandy-Walker malformation and aqueductal obstruction have been treated with third ventriculostomy and stent placement from the third ventricle to the posterior fossa cyst. 39,40 Tumour biopsy (including pineal and tectal tumours), CSF sampling and treatment of associated hydrocephalus can be accomplished with transventricular endoscopic biopsy and third ventriculostomy in the setting of intra and paraventricular tumours. [41][42][43][44][45][46][47][48] One investigator described relief of hydrocephalus and reported gradual resolution of enhancing tectal tumours after third ventriculostomy in two children.…”
Section: Indicationsmentioning
confidence: 99%
“…Valera et al [15 ]reported two cases of initially inoperable pilocytic astrocytoma in which preoperative neoadjuvant chemotherapy eased the surgical resection. Further, Cartmill et al [16 ]presented a case of hypervascular pleomorphic xanthoastrocytoma that was completely removed 9 weeks after preoperative chemotherapy. Regardless of these positive reports on the usefulness of preoperative chemotherapy, to our knowledge, there have been no reports on the advantages of preoperative radiotherapy for subsequent surgical removal of brain stem JPA.…”
Section: Discussionmentioning
confidence: 99%